Analisis Pentingnya Kompensasi Pensiun dan Tabungan Hari Tua Sebagai Hak Peserta PT Taspen (Persero) - Wanti, Nur Aulia Silvia; Yani, Mutiara Firda; Anggraini, Risma; Hidayati, Nur; Huda, Bias Miftahul; S, Saridawati (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
One of the best methods to prepare to earn income in retirement is to join a pension program. The aim of this research is to find out how important pension compensation and old age savings are. The method used in this research is descriptive qualitative research, namely in the form of written sentences and facts spoken by the resource person through interviews and the behavior of the resource person that the researcher has observed. The data obtained by researchers is secondary, obtained from articles, books and journals. The results obtained show that pension compensation and old-age savings are very important as old-age security because the existence of pension funds can provide many benefits for the recipients.